Biochemical Implication of Long Term Administration of Halofantrine Hydrochloride (Halfan) on Estradiol Levels of Female Wistar Rats - Ugochukwu, C.N.C.; Ebong, P.E.; Eyong, E.U. (Pakistan Journal of Nutrition, 2008)
This study determined the influence of doses of halofantrine hydrochloride, a phenanthrene methanol drug used in the therapeutic treatment of malaria on the estradiol levels of female wistar rats. A suspension of the drug at a dose of 0.5ml/kg and 1ml/kg body weight three times at six hourly intervals were administered orally to different groups of mature female rats for 5 and 10 days duration, control groups received similar treatment doses of normal saline. The animals were sacrificed on the 5th and 10th day after drug administration by cervical dislocation. Whole blood samples were collected for white blood cell count. From the plasma, the hormonal level was determined by radio-immunoassay and the activities of AST, ALT and ALP were also determined. The level of estradiol following 5 and 10 days treatment was higher significantly (p